PERANAN TENTANG NILAI GOTONG ROYONG SEBAGAI BENTUK PENERAPAN SILA KE-TIGA PANCASILA DI DESA WONOREJO KECAMATAN BANYUPUTIH KAB. SITUBONDO - Bayu Indra Permana; Agus Mursidi (Citizenship Jurnal Pancasila dan Kewarganegaraan, 2020)
Mutual cooperation is a social activity and a characteristic of the Indonesian people. As stated in Pancasila, the third principle is "Indonesian Unity". Mutual cooperation is the nation's personality that has firm roots in people's lives. The existence of mutual cooperation grows from our own, the behavior of the community. This study aims: 1) To find out the role of mutual cooperation values in Wonorejo Village as a form of the implementation of the third precept, 2) to be input and terms of reference regarding unity and mutual cooperation in Wonorejo Village, Banyuputih District. The research method used is descriptive qualitative method. This research is purposive sampling method. sampling technique using snawball sampling from community and religious leaders. The results of this study indicate that mutual cooperation is still applied in Wonorejo Village as evidenced by the activities of mutual cooperation that still exist even though the value of mutual cooperation is not fully operational because it is influenced by foreign cultures that come in and some people do not understand the importance of mutual cooperation.